Aspiration of acidified milk induces milk allergy by activating alveolar macrophages in mice - Akiko Nakaoka; Takayasu Nomura; Atsushi Suzuki; Kazuyoshi Ozeki; Hirohito Kita; Shinji Saitoh (Allergology International)
Background: Epidemiological studies have identified associations between gastroesophageal reflux (GER) and cow's milk allergy (CMA) in infants. However, the role of GER in the development of CMA remains poorly understood. Our primary objectives were to develop a mouse model that suggests GER as a potential pathogenic mechanism for CMA and to elucidate the immunological mechanisms that connect lung innate immunity with CMA. Methods: Mice were exposed to cow's milk (CM) treated with hydrochloric acid through repeated aspiration into their airways. Subsequently, they were challenged by intraperitoneal injection of CM extract. The immunological mechanisms were investigated using comprehensive single-cell RNA sequencing (scRNA-seq) analysis of the lungs, combined with the use of genetically modified mice. Results: Mice exposed to CM mixed with hydrochloric acid via airway sensitization developed CMA, as evidenced by the production of antigen-specific IgE and IgG antibodies, and the induction of anaphylaxis upon systemic antigen administration. In contrast, aspiration of CM alone did not induce CMA. scRNA-seq analysis revealed potential roles of alveolar macrophages in response to hydrochloric acid. Mice lacking the TLR4 pathway were protected from developing CMA. Conclusions: We have developed a novel mouse model for CMA that utilizes the natural antigen and follows the physiological airway sensitization pathway, thus potentially resembling clinical scenarios. This model, named the acidified milk aspiration-induced allergy model, has the potential to shed light on the role of early innate immunity by analyzing a more physiological model.